PALEOCLIMATIC RECORD IN THE LATE SENOZOIC SEDIMENTS OF LAKE BAIKAL: (BY 600 M DEEP-DRILLING DATA) - Antipin V.; Afonina T.; Badalov O.; Bezrukova E. (My University, 2000)
Drilling experiments were performed in 1998 on the Akademichesky Ridge at 53 degrees 44'48 " N and 108 degrees 20'34 " E. The borehole depth was 670 m, the water depth was 333 m. Continuous core sampling was performed to a depth of 600 m. Core recovery was 95%. The sediments of the section consist of biogenic and terrigenous muds. Clay beds alternate with beds rich in diatom frustules throughout the section. This rhythmic structure, observed to the end of the section, is related mainly to alternation of warm and cold periods. The variation in diatom content is accompanied by variations in the content of biogenic silica, magnetic susceptibility, humidity, and density of the sediments. Paleomagnetic studies of the section and analysis of orbital frequencies of the Earth in the climatic record of the core permit the sediments lying at a depth of 600 m to be dated at 10.3 Ma. The results obtained provide a base for further detailed climatic reconstructions in Central Asia starting from the end of the Middle Miocene and for refinement of the geologic history of the Baikal Rift.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен